PENGARUH SUBSTITUSI PET DAN ABU BUNGA PINUS MENGGUNAKAN METODE PENCAMPURAN BASAH DAN METODE PENCAMPURAN KERING PADA CAMPURAN LASTON AC-WC TERHADAP STABILITAS - Illiyyuna Diazshafa Marwati; Nia Indria; Lulusi Lulusi; Alfi Salmannur (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2021)
Consumption of plastic waste in Indonesia is very high disrupting environmental sustainability, plastic waste takes hundreds of years to decompose making it a problem to be addressed immediately. So, in recent times, research has been carried out to utilize plastic waste into plastic-mix asphalt technology. One of them is by modifying the asphalt mixture with plastic bottle waste the type of Polyethylene Terephthalate (PET) as an additive. In addition, this study also used additional filler in the form of pine flower ash (PFA). This study aims to determine the characteristics of the AC-WC asphalt concrete mixture through Marshall testing of the substitution of PET into 60/70 penetration asphalt and filler ABP with  using wet mixing methods and dry mixing methods. This research was started by examining the physical properties of asphalt, modified asphalt, and aggregates. Furthermore, the manufacture of test specimens with variations in asphalt content was carried out to determine the optimum bitumen content (OBC) and obtained OBC values of 5.29%, 5.79%, and 6.29%. Then made a PET substitution test object of 3%, 5%, and 7% and a combination of filler PFA 6% of the total weight of the filler on each asphalt content with wet mixing method and dry mixing method through Marshall test. The results of this study indicate that the stability for both methods of mixing the best levels is found in the substitution of 7% PET and the combination of ABP filler with an asphalt content of 6.29%, 1226.12 kg for the wet mixing method and 1291.43 kg for the dry mixing method. The durability value for the wet mixing method was obtained at 90.87% and for the dry mixing method it was obtained at 91.55%, both of these durability tests had met the specifications of 90%.